JAMUR PEMBENTUK GAHARU SEBAGAI PENJAGA KELANGSUNGAN HIDUP TANAMAN GAHARU (Aquilaria sp) - Subowo, Yohanes Bernard (Jurnal Teknologi Lingkungan, 2010)
Agarwood is economical important non forest timber product. The objective of this research was to obtain fungi that have ability to effectively infect and form agarwood.The fungi were isolated and selected from agarwood for effective infection studies.Ten isolates were successfully isolated, they were belonging to Aspergillus (JG5, JG17,KT17, JG31, JG32, JG21, JG19), Penicillium (JG4), Fusarium (JG12, JG18). Four isolates were successful form effective infection and they identified as Aspergillus sp JG17, Aspergillus sp JG31, Aspergillus sp JG32 and Fusarium sp JG12. They produced secondary metabolite. The Fusarium sp JG12 was the most effective strain produced agarwood and form resin gaharu on Aquilaria beccariana after 4 months inoculation. The size of agarwood formed was 2,96 cm in length and 0,16 cm wide. It is recommendedto use this strain for effective formation of agarwood.Key words: isolation, fungi, agarwood, Fusarium